Outcome on liability in the case of commercial companies - Aranda Rodríguez, Ana María (2008)
The imputation of the damages produced by the mercantile societies through its constituent organs, it has had diverse approaches, as much in the doctrinary scope as in the legal. The present article tries to make some reflections and to establish that if the indicated legal person causes damages by the acts of its constituent organs, these are not refered to the acting of others, and it is this society that must assume the responsibility, therefore the rules referring to the responsibility of the subordinate do not apply, but rather the rules that contain the principle of not causing harm to anyone.